2022
DOI: 10.15826/chimtech.2022.9.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Proton-conducting membranes based on CsH2PO4 and copolymer of tetrafluoroethylene with vinylidene fluoride

Abstract: In this work, proton conductivity, morphology and mechanical properties of (1–x)CsH2PO4–xF-42 (x=0.05–0.3, weight ratio) membranes were investigated for the first time. Thin flexible membranes for x≥0.15 with the uniform distribution of the components were obtained by a tape casting method. Mechanical properties of the membranes were measured by Vickers microhardness tests for a low polymer content (x˂0.15), also the tensile strength for membranes with high polymer content x=0.2–0.3 were evaluated. Proton cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It was shown that the P2 1 /m structure of the acid salt was retained in the composite electrolytes with different FPs (UPTFE, F42, SKF26, and PVDF) [ 27 , 31 , 32 , 33 ]. A more intensive peak in relation to the polymer can be observed on the PXRD patterns only at x ≥ 0.15 for the membranes based on FPs with a sufficiently high degree of crystallinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the P2 1 /m structure of the acid salt was retained in the composite electrolytes with different FPs (UPTFE, F42, SKF26, and PVDF) [ 27 , 31 , 32 , 33 ]. A more intensive peak in relation to the polymer can be observed on the PXRD patterns only at x ≥ 0.15 for the membranes based on FPs with a sufficiently high degree of crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD pattern for fluoroelastomer SKF26 consists of only an amorphous halo at 2Θ~17 • due to the low crystallinity owing to bulky HFP parts in a VDF structure. It was shown that the P2 1 /m structure of the acid salt was retained in the composite electrolytes with different FPs (UPTFE, F42, SKF26, and PVDF) [27,[31][32][33]. A more intensive peak in relation to the polymer can be observed on the PXRD patterns only at x ≥ 0.15 for the membranes based on FPs with a sufficiently high degree of crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of fluoropolymers make their use as dopants for cesium dihydrogen phosphate promising. Earlier the reports were made of “CDP—fluoropolymer” systems, where such polymers as ultrafine polytetrafluoroethylene (UPTFE), polyvinylidene fluoride (PVDF), VDF copolymers with hexafluoropropylene (SKF-26), with tetrafluoroethylene (F-42), were used as additives [ 26 , 28 , 33 , 34 ]. Specifically, fluoroplastic-2M, with a commercial name F-2M, can be used as it consists of modified PVDF composition.…”
Section: Introductionmentioning
confidence: 99%